Proposal of a Method for Detection of a Damaged Hydraulic Shock Absorber in a Vehicle’s Suspension System - Mykola Gorbunov; Ján Dižo; Miroslav Blatnický; Kateryna Kravchenko; Stanislav Semenov; Evgeny Mikhailov (Communications - Scientific letters of the University of Zilina, 2022)
In principle, every vehicle is equipped by a suspension system, which usually consists of springs and shock absorbers. The main purpose of the suspension system is to eliminate vibration of sprung and unsprung masses. Therefore, the proper operation conditions of the shock absorbers affect in a fundamental way total running properties of vehicles. However, during operation, shock absorbers are being worn out or they can even be damaged. Then, such a situation is unwanted and it has to be detected as soon as possible. The content of this article is focused on analysis of vehicles’ shock absorbers defects. Methods for detection of possible shock absorbers faults are presented. Further, a proposal of the method for detection of a state of a hydraulic shock absorber during its operation is presented. The method uses identification of the temperature change of a hydraulic shock absorber during operation.